Antifunctionality in Shawi split ergativity, a processing analysis - Rojas-Berscia, Luis Miguel; Bourdeau, Corentin; Grondelaers, Stefan; Seuren, Pieter A. M. (Revista Brasileira de Linguística Antropológica, 2023)
In this article, as a follow-up of Rojas-Berscia and Bourdeau (2017), we study morphological ergativity in Shawi (Kawapanan) using a dedicated experimental design. Shawi displays ergative-marking in an opposite direction from Silverstein’s Nominal Hierarchy (NH) (Silverstein 1976). We claim this pattern to be antifunctional, given the lack of internal syntactic cues that explain why ergativity is omitted or completely obligatory in cases where the NH predicts the opposite. To test this hypothesis, we carried out a grammaticality judgment experiment in the field with 47 Shawi participants from four sites. We found a significant overall effect of the Antifunctional Ergativity Constraint Expectation (AECE): sentences that violated this constraint were in general deemed less acceptable. Finally, we provide a tentative hypothesis on the historical origin of this pattern, resorting to discussions on the origins of ergativity in historical syntax (Gildea 2004; Gildea and Queixalós 2010), the reconstruction of Proto-Kawapanan morphosyntax, and antifunctional patterns in language (Seuren and Hamans 2010).